THE ROLE OF NEOPTERIN AS A NOVEL BIOMARKER FOR REDUCED KIDNEY FUNCTION: A COMMUNITY BASED STUDY - Widiana, G Raka; Suwitra, K; Effendi, Imam (journal of internal medicine, 2011)
Cardiovascular disease is a major complication for patents with reduced kidney function. Neopterin is well known as abiomarker for cardiovascular disease, however it is not clear whether it is associated with reduced kidney function. Study wascarried out in a Legian Kuta village a tourist town in Bali. Samples were underwent a series of interview, physical examinationand were taken blood samples for neoperin and creatinine tests. Neoptein concentrations were tested for its normal distributionand associated with C-G formula for estimated glomerular filtration rate. Cut-off value for prediction of reduced renal functionwas rested using ROC curve, and calculated for sensitivity, specificity.Seventy nine samples were selected through cluster random sampling from 284 residents (177 males and 107 females)with age 46 ± 10 years, body weight 67 ± 13 kg and height 162 ± 9 cm. It was shown that neopterin concentration was normallydistributed (K-S Z = 1.175, p = 0.126), with mean 6.66 ± 3.35 ng/ml and e-GFR was 89 ± 25 ml/mnt. There was significantnegatively correlation between neopterin concentrations and e-GFR (R = -0.26, Rsq = 0.068, p = 0.021), using regressionequation it was revealed that every 1 unit increased of neopterin concentrations produce 1.42 decrease of e-GFR. Using ROCcurve, neopterin was accurately detect reduced kidney function defined as e-GFR of 60 ml/mnt or less (AUC = 0.88; 95%CI0.74 to 1.00; SE = 0.07; p = 0.02). Using 7.46 ng/ml as cut-off value for normal neopterin concentrations, it was showed thatsensitivity and specificity were 100% and 72% to detect the presence of reduced kidney function, consecutively. Neopterin maybe used as a novel biomarker for reduced kidney function, for its role in the pathogenesis of cardiorenal syndrome in generalpopulation.